Gender and development research cluster :Growth and involvement of women entrepreneurs in the informal sector in Tanzania - Tundui, H. P (Mzumbe university, 2026)
Introduction anointment a BUK СКDB the involvement of women in entrepreneurship in Tanzania has increased tremendously since the mid-1980s and now has become the main source of employment and income for the majority of women in the country. What is evident is that the increased participation of women in entrepreneurship has not only altered women's access to economic resources and cash incomes, but has also brought about other socio-cultural challenges. Despite their involvement in entrepreneurship, women have difficulties in accessing credit markets necessary for starting, improving and expanding their enterprises, either due lack of knowledge and skills required to access credits or credit conditions. It is from this context that, the study was proposed to explore the factors that determine women's assess to credit sources in Tanzania. The purpose of this research was to study the factors that determine the likelihood of women enterprises in Tanzania using credits as sources of finance and examine terms of credit, including interest rates, and collateral requirements, to determine whether the lending conditions imposed on women business owners in Tanzania are more stringent and different from those imposed on men.